(untitled) - Webman, Jerry A. (Hoboken, N.J., 2012)
The financial world is changing; this book shows you how to update your ideas about investing and keep pace Investing successfully means figuring out where economic value is being created, and then identifying the investment opportunities that result.
Keywords: Investments,Đầu tư